2011
DOI: 10.1161/circulationaha.111.029892
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Novel Aldosterone Synthase Inhibitor for Treatment of Primary Hypertension

Abstract: Background-LCI699, a novel inhibitor of aldosterone synthase, reduces serum aldosterone, and may have benefit in the treatment of hypertension. Methods and Results-We performed the first double-blind, randomized trial with LCI699 in patients with primary hypertension. We randomized 524 patients to LCI699 0.25 mg once daily (nϭ92), 0.5 mg once daily (nϭ88), 1.0 mg once daily (nϭ86), and 0.5 mg twice daily (nϭ97); eplerenone 50 mg twice daily (nϭ84); or placebo (nϭ77) for 8 weeks. Adrenocorticotropic hormone (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(60 citation statements)
references
References 32 publications
2
58
0
Order By: Relevance
“…32 An 8-week placebo-controlled doseresponse study in patients with stage 1 and 2 essential hypertension reported an optimal decrease in BP with a dose of 1 mg LCI699 o.d., which had an antihypertensive effect similar to that of eplerenone 50 mg b.i.d. 33 However, LCI699 administration was associated with biological signs of partial inhibition of the glucocorticoid axis, as shown by the dose-related increase in both plasma ACTH and in 11-deoxycortisol concentrations, the cortisol precursor, consistent with an inhibition of the CYP11B1 gene product. 31 Nevertheless, the clinical and biological safety and tolerability of LCI699 were similar to those of placebo and eplerenone.…”
Section: New Ways To Target the Aldosterone Pathway: Aldosterone Syntmentioning
confidence: 93%
See 1 more Smart Citation
“…32 An 8-week placebo-controlled doseresponse study in patients with stage 1 and 2 essential hypertension reported an optimal decrease in BP with a dose of 1 mg LCI699 o.d., which had an antihypertensive effect similar to that of eplerenone 50 mg b.i.d. 33 However, LCI699 administration was associated with biological signs of partial inhibition of the glucocorticoid axis, as shown by the dose-related increase in both plasma ACTH and in 11-deoxycortisol concentrations, the cortisol precursor, consistent with an inhibition of the CYP11B1 gene product. 31 Nevertheless, the clinical and biological safety and tolerability of LCI699 were similar to those of placebo and eplerenone.…”
Section: New Ways To Target the Aldosterone Pathway: Aldosterone Syntmentioning
confidence: 93%
“…31 Nevertheless, the clinical and biological safety and tolerability of LCI699 were similar to those of placebo and eplerenone. 33 The effects of LCI699 on the glucocorticoid axis limit the use of higher doses in hypertension because of the loss of selectivity for CYP11B2. Therefore, this aldosterone synthase inhibitor will not be able to replace MR blockade in patients with hypertension, but is now being evaluated at much higher doses in Cushing syndrome.…”
Section: New Ways To Target the Aldosterone Pathway: Aldosterone Syntmentioning
confidence: 99%
“…In early clinical trials, it was observed that while at low doses it is a potent and selective inhibitor of aldosterone synthetase, at higher doses it also inhibits 11b-hydroxylase (CYP11B1 product) (104,105). Following treatment with LCI699, hypertensive patients, either due to primary hyperaldosteronism or essential hypertension, showed a reduction in blood pressure associated with a dose-dependent decrease in plasma and urine aldosterone (up to 80%) and an increase in 11-deoxycorticosterone (104,105,106). At doses of 0.5-1 mg, daily there was an increase in steroid precursors 11-deoxycorticosterone and 11-deoxycortisol and a blunting of the cortisol response to synthetic ACTH, indicating inhibition of 11b-hydroxylase (104,105).…”
Section: Lci699mentioning
confidence: 99%
“…It also inhibits 11b-hydroxylase (CYP11B1) in a similar manner to the R-enantiomer of fadrozole (FAD286) that blocks the hydroxylation of deoxycortisol to cortisol as well as CYP11B2 blocking the conversion of deoxycorticosterone to corticosterone ( Fig. 2) (Calhoun et al 2011). LCI699 is currently under investigation as a treatment for CD (Tritos et al 2011, Feelders & Hofland 2013.…”
Section: Lci699mentioning
confidence: 99%